When ear squats were fun - Abd Razak, Dzulkifli (2005)
YESTERDAY, Dec 10, was International Human Rights Day. Human rights has been making headlines recently. However, none is as hotly debated as the nudesquat issue. Attached to it is an unpleasant image, in fact a dehumanising one. Ketuk ketampi is the Malay word to describe squats done repeatedly, usually as punishment. This has been practised for a long time in our society without much fuss, let alone being linked to human rights abuse. What has changed? The Kamus Dewan (2000) definition of ketampi is a kind of bird, an owl of the genus Ketupa, which recently has been changed to Bubo. It is said to be related to the commonly named Brown Fish Owl. It is similar to a local owl called the Buffy or Malay Fish Owl, Bubo (Ketupa) ketupu, a popular species that had made it on a Malaysian stamp collection as Burung Hantu Kuning.